Answer: Answer is in the attachment xoxo
Step-by-step explanation:Subtract
y
2
y
2
from both sides.
16
x
−
4
y
=
−
20
−
y
2
16x−4y=−20−y
2
2 Factor out the common term
4
4.
4
(
4
x
−
y
)
=
−
20
−
y
2
4(4x−y)=−20−y
2
3 Divide both sides by
4
4.
4
x
−
y
=
−
20
−
y
2
4
4x−y=
4
−20−y
2
4 Add
y
y to both sides.
4
x
=
−
20
−
y
2
4
+
y
4x=
4
−20−y
2
+y
5 Divide both sides by
4
4.
x
=
−
20
−
y
2
4
+
y
4
x=
4
4
−20−y
2
+y
6 Simplify
−
20
−
y
2
4
+
y
4
4
4
−20−y
2
+y
to
−
20
−
y
2
4
4
+
y
4
4
4
−20−y
2
+
4
y
.
x
=
−
20
−
y
2
4
4
+
y
4
x=
4
4
−20−y
2
+
4
y
7 Simplify
−
20
−
y
2
4
4
4
4
−20−y
2
to
−
20
−
y
2
4
×
4
4×4
−20−y
2
.
x
=
−
20
−
y
2
4
×
4
+
y
4
x=
4×4
−20−y
2
+
4
y
8 Simplify
4
×
4
4×4 to
16
16.
x
=
−
20
−
y
2
16
+
y
4
x=
16
−20−y
2
+
4
y